Las Adaptaciones Curriculares y su Influencia en el Proceso de Aprendizaje en los Estudiantes con Necesidades Educativas Específicas (NEE) en la Unidad Educativa del Milenio José de San Martín, Ventanas. 2023 - Gavilanes Osorio, Yuri Cecibel (2024)
This research focuses on the incidence of curricular adaptations in the learning of students with specific educational needs not associated with disability, it has been the reality of school classrooms all the time, that is why it aims to determine the flexibility of curricular adaptations and their influence on the learning process in students with specific educational needs in the José de San Martín Millenium School, Ventanas, 2023, in which in its methodological section has a non-experimental design and with a field research type applied in an educational unit, Institution, the quantitative approach with a descriptive and causal explanatory scope to identify the incidence of curricular adaptations in learning, the SPSS statistic is applied for data processing in which it is evident that by its level of significance there is correlation between the variables of the proposed study, The conclusion is that curricular adaptations affect the learning process of students with specific educational needs not associated with disability, so that students can access the curriculum and participate actively in the classroom, adjusting the activities and materials to their abilities and difficulties.